THE ARTISTIC SKILLS OF ERNEST HEMINGWAY (Intent Research Scientific Journal, 2023)
Ernest Miller Hemingway is a bright representative of American literature of the 20th century. The winner of the Nobel Prize (1954), the author of the most widely translated and recognized works “Fiesta”, “A Farewell to Arms”, “The old man and the sea”.